1993
DOI: 10.1128/jb.175.19.6299-6313.1993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of acrA and acrE genes of Escherichia coli

Abstract: The DNA fragment containing the acrA locus of the Escherichia coli chromosome has been cloned by using a complementation test (4,24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
343
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(359 citation statements)
references
References 40 publications
11
343
0
1
Order By: Relevance
“…All of these are so-called membrane fusion proteins (MFPs) of RNDtype multidrug efflux transporters. The analysis also showed VmeB to share 63, 63, 62, 62 and 61 % identities, respectively, with AcrB, AcrD and AcrF of E. coli (Klein et al, 1991;Ma et al, 1993Ma et al, , 1994, SdeY of S. marcescens (Chen et al, 2003) and MexB of P. aeruginosa (Poole et al, 1993). These are inner-membrane proteins of RND-type multidrug efflux transporters.…”
Section: Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these are so-called membrane fusion proteins (MFPs) of RNDtype multidrug efflux transporters. The analysis also showed VmeB to share 63, 63, 62, 62 and 61 % identities, respectively, with AcrB, AcrD and AcrF of E. coli (Klein et al, 1991;Ma et al, 1993Ma et al, , 1994, SdeY of S. marcescens (Chen et al, 2003) and MexB of P. aeruginosa (Poole et al, 1993). These are inner-membrane proteins of RND-type multidrug efflux transporters.…”
Section: Sequencingmentioning
confidence: 99%
“…All these differences were translationally silent, except two: changing amino acid residue Gly33 in VP1091 to Ala33 in VmeA, and changing Ala1046 in VP1092 to Asp1046 in VmeB. A BLAST search for protein sequence similarities (NCBI) showed VmeA to share, respectively, 49, 49, 47 and 46 % identities with AcrA and AcrE of E. coli (Klein et al, 1991;Ma et al, 1993), SdeX of Serratia marcescens (Chen et al, 2003) and MexA of Pseudomonas aeruginosa (Poole et al, 1993). All of these are so-called membrane fusion proteins (MFPs) of RNDtype multidrug efflux transporters.…”
Section: Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, other tetracycline derivatives were similarly affected by AcrAB and/or AcrEF, with two-to fourfold increases in the MICs (Table 3). AcrB is the highly potent MDR transporter in E. coli, and AcrF is its close homologue; the amino acid identity between the two is 77% (13). Bcr expression did not result in any change in the tigecycline MIC.…”
Section: Induction Of Tet(b) By Tigecycline In E Coli W3104/plgt2 [Tmentioning
confidence: 99%
“…Many PEPs, such as the hemolysin translocator accessory protein HlyD (Felmlee et al, 1985), have a stretch of hydrophobic residues near the N terminus believed to span the cytoplasmic membrane (Schu È lein et al, 1992). Others, like AcrA and AcrE of E. coli (Ma et al, 1993) and MexA of P. aeruginosa (Poole et al, 1993) have a lipoprotein modi®cation signal and are likely to insert in the cytoplasmic membrane via an attached lipid moiety (Dinh et al, 1994;Seiffer et al, 1993). PEPs appear to form trimers (Thanabalu et al, 1998), and have been shown to interact speci®cally with OEPs (Akatsuka et al, 1997;Binet & Wandersman, 1995;Hwang et al, 1997;Le Âtoffe  et al, 1996).…”
Section: Introductionmentioning
confidence: 99%